2009
DOI: 10.1590/s0101-20612009005000004
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antioxidante de pimentas do gênero Capsicum

Abstract: Naturalmente os alimentos estão em constantes modificações, representadas por alterações físicas, enzimáticas, microbiológicas e químicas, como as reações de oxidação de lipídios e outros nutrientes susceptíveis à ação do oxigênio e radicais livres, provocando por sua vez o aparecimento de sabores e odores desagradáveis, modificações do valor nutricional e a diminuição da vida de prateleira dos alimentos.Para retardar tais processos, a indústria faz uso de aditivos químicos constantemente questionados pelos co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
20
0
7
Order By: Relevance
“…In this study, the initial total phenolic content was 240 ± 27 mg galic acid equivalents/100 g sample, which was very close to the value obtained by Oboh and Rocha (2007) (218 mg/100 g of sample) and higher than the value found by Hassimotto, Genovese and Lajolo (2005) (131 mg/100 g sample) in methanolic extract of C. annuum. Costa et al (2010) also found lower values of total phenolic content in four different types of peppers (chillies, Magali red, cambuci, and cumari peppers), when analyzing pepper extract using different solvents (hexane, chloroform, and ethyl acetate). Deepa et al (2007) found total phenolic content between 323 and 852 mg/100 g sample for 10 different species of C. annuum L., and Howard et al (2000) found values ranging from 284.6 to 570.7 mg/100 g in ripe fruits of four species of C. annuum.…”
Section: Total Phenolic Contentmentioning
confidence: 82%
See 2 more Smart Citations
“…In this study, the initial total phenolic content was 240 ± 27 mg galic acid equivalents/100 g sample, which was very close to the value obtained by Oboh and Rocha (2007) (218 mg/100 g of sample) and higher than the value found by Hassimotto, Genovese and Lajolo (2005) (131 mg/100 g sample) in methanolic extract of C. annuum. Costa et al (2010) also found lower values of total phenolic content in four different types of peppers (chillies, Magali red, cambuci, and cumari peppers), when analyzing pepper extract using different solvents (hexane, chloroform, and ethyl acetate). Deepa et al (2007) found total phenolic content between 323 and 852 mg/100 g sample for 10 different species of C. annuum L., and Howard et al (2000) found values ranging from 284.6 to 570.7 mg/100 g in ripe fruits of four species of C. annuum.…”
Section: Total Phenolic Contentmentioning
confidence: 82%
“…Other studies focused on product quality aimed to investigate the effect of the temperature on the composition of pepper (FAUSTINO; BARROCA; GUINÉ, 2007), especially with respect to vitamin C, phenolic compounds, carotenoids (DI SCALA;CRAPISTE, 2008;COSTA et al, 2010;MONTES et al, 2010), color, and antioxidant properties (ARSLAN; ÖZCAN, 2011).…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, DPPH has the advantage of being unaffected by certain side reactions of polyphenols, such as metal ion chelation and enzyme inhibition (Holtekjolen, Kinitz, & Knutsen, 2006). ABTS assay is based on a stable ABTS radical cation which has a blue-green chromophore absorption, produced by ABTS oxidation with potassium persulfate and is reduced in hydrogendonating antioxidants (Costa, Moura, Marangoni, Mendes, & Teixeira, 2010). Although this method has a similar mechanism to the DPPH assay, the ABTS assay in current investigation presented a higher value when compared to that of the DPPH test (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…They present high concentrations of vitamins A, C and E (Kuda et al, 2004) and recent studies indicate significant antioxidant activity and phenolic content in some species of the genus Capsicum (Costa et al 2010;Materska and Perucka, 2005).…”
Section: Introductionmentioning
confidence: 99%